Structural and Temporal Patterns-Based Features - Ranganath, Venkatesh-Prasad; Thomas, Jithin (Proceedings of International Workshop on Data Analysis Patterns in Software Engineering (DAPSE) 2013, 2013)
In this paper, we propose a data transformation pattern to transform sequential data into a set of binary/categorical features and numerical features to enable data analysis. These features capture both structural and temporal information inherent in sequential data.